TINJAUAN PROSEDUR AUDIT ATAS HUTANG JANGKA PENDEK PADA KLIEN KAP TENDY WATO & IFEN TJHAI - Sinta Dwi Wulandari, - (2018)
The three-month Field Work Practice at KAP Tendy Wato & Ifen Tjhai is a public accounting firm that audits the financial statements of companies. During the field work practice, the authors are placed in Staff Tax & Audit and the authors conduct activities related to audit on PT.X which is one of KAP clients Tendy Wato & Ifen Tjhai, starting from the process of vouching, checking tax invoice, check payment debt, looking for documents related to the data being examined. In carrying out fieldwork practices, the authors get various benefits obtained such as knowledge and increased insight into the autit procedure on PT.X as well as experiences that the author did not get in college. Especially performing audit procedures on short-term debt which is conducting an assessment of various short-term debt in accordance with existing document.